Positron spectroscopy of defects in submicrocrystalline nickel after low-temperature annealing; Physics of the Solid State; Vol. 57, iss. 2 - Kuznetsov P. V. Pavel Viktorovich; Mironov Yu. P.; Tolmachev A. I.; Bordulev Yu. S. Yuri Sergeevich; Laptev R. S. Roman Sergeevich; Lider A. M. Andrey Markovich; Korznikov A. V. (2015, 2015)
Title screen